Audience segmentation and climate change communication: conceptual and methodological considerations. (19th March 2014) - Hine, Donald W; Reser, Joseph P; Morrison, Mark; Phillips, Wendy J; Nunn, Patrick; Cooksey, Ray
<x xml:space="preserve">Abstract</x> Engaging the public about mitigating or adapting to climate change threats poses significant challenges for scientists, policy makers, and others responsible for developing communication strategies. In response to these challenges, interest is growing in audience segmentation as a possible strategy to develop more effective communications that are tailored and targeted to subgroups of the public who share similar values, beliefs, behaviors, and/or policy preferences about climate change. In this article, we provide a brief historical overview of audience segmentation and its applications to marketing, health, politics, and most recently climate change. We then critically evaluate several conceptual arguments about whether segmentation is an appropriate strategy for climate change communications, review key methodological considerations associated with conducting segmentation analyses, and make several recommendations about best practice. We conclude that, in principle, audience segmentation and targeted messaging are potentially valuable tools for enhancing climate change communication. But, in practice, there are conceptual and methodological complexities of which practitioners and consumers should be aware when conducting and interpreting the results of segmentation studies. In addition, more research is required, particularly related to tailoring and targeting messages to identified segments, before these strategies can be considered to have a sufficient evidence base to warrant widespread adoption. For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.